Nasionalisasi Garuda Indonesia, 1950—1958 - Dwi Adi Wicaksono (Universitas Gadjah Mada, 2016)
This article discusses the efforts of the decolonization of civil aviation by the Government of Indonesia from 1950 to 1958 through the nationalization of Garuda Indonesia joint venture airlines. The discussion of this article focuses on the explanation of the process of nationalization and its impact on the developmentof the airline. During this period, the nationalization efforts against Garuda Indonesia Airlines tended to be heavily influenced by the political policies of the two ruling Cabinet, that is Masyumi and PNI. This shows a great political tendency to the nationalization agenda of the civil aviation company. The nationalization ofGaruda Indonesia tends to exhibit a complex set of processes, because in addition to the transfer of government share ownership, the takeover of this company also requires a long process to get the human resources ready to operate the airline as a whole. At this stage, Indonesianization is of the utmost importance in the nationalization process of Garuda Indonesia.